Medidas de ressonância paramagnética eletrônica no \'ALFA\'-\'NI\' s\'O IND.4\'.6\'H IND.2\'o - Pontuschka, Walter Maigon (1973)
Medidas de ressonância paramagnética eletrônica no \'ALFA\'-\'NI\' s\'O IND.4\'.6\'H IND.2\'o